2020
DOI: 10.1016/j.matcom.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Using skeleton and Hough transform variant to correct skew in historical documents

Abstract: As a main part of several document analysis systems, Skew estimation represents one of the major research defies, particularly in case of historical documents exploration. In this paper, we propose an original skew angle detection and correction technique. Morphological Skeleton is introduced to considerably diminish the amount of data by eliminating the redundant pixels and preserving only the central curves of the image components. Next, the proposed method uses Progressive Probabilistic Hough Transform (PPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Figure 6 shows that the ATOP80 value of our method is 0.081, which is much smaller than that of the SHT method and PP method, and is only 0.3 larger than that of the-state-of-art method (Boudraa's method). In addition, from the experimental results of [38], we can see that the computational time of Boudraa's method is greater than that of SHT method and similar to the computational time of PP method. From Figure 6, we can see that our method is much faster than SHT method and PP method.…”
Section: Comparison Of Accuracymentioning
confidence: 73%
See 2 more Smart Citations
“…Figure 6 shows that the ATOP80 value of our method is 0.081, which is much smaller than that of the SHT method and PP method, and is only 0.3 larger than that of the-state-of-art method (Boudraa's method). In addition, from the experimental results of [38], we can see that the computational time of Boudraa's method is greater than that of SHT method and similar to the computational time of PP method. From Figure 6, we can see that our method is much faster than SHT method and PP method.…”
Section: Comparison Of Accuracymentioning
confidence: 73%
“…In Boudraa's method [38], to validate the inclination angle estimation performance, they used some indicators to valuate and compare their experiment results. In our experiment, we used the same indicators.…”
Section: Evaluation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The Hough Line Detection algorithm [6,7,8,9,10], utilised in the aforementioned algorithm, involves the following steps:…”
Section: Related Workmentioning
confidence: 99%
“…This is non-contact angle detection from a digital image. For example, while Hough transform has been frequently applied to detect the skew angle of the characters in documents (Amin and Fischer, 2000;Singh et al, 2008;Boukharouba, 2017;Boudraa et al, 2020) and to evaluate the rotation of loosened bolts (Park et al, 2015;Cha et al, 2016;Pham et al, 2020;Ta and Kim, 2020), it has found applications in the measurement of contact angle between liquid and solid interface (Xu et al, 2013) and in the estimation of muscle fiber orientation in the medical field (Zhou and Zheng, 2008).…”
Section: Introductionmentioning
confidence: 99%